Purification and characterization of surfactant-stable protease from Bacillus lichenformis: A potential additive for laundry detergent - Mardina, Vivi; Yusof, Faridah (Bio IT journal, 2016)
This study purified and characterized the protease from Bacillus licheniformis that was cultured in skim latex serum fortified media. Ammonium sulphate precipitation and ion exchange chromatograph was employed in purification steps with the enzyme activity increase to 2.28 fold of purification compare to the crude enzyme. Assessment of the purified protein by SDS PAGE showed a single band with molecular mass of about 47 kDa. The enzyme was stable at temperature range of 35 oC to 65 oC and also at pH 6.0 and 7.0 for 60 min. The presence of Mn2+ and Ca2+ ions in the produced protease stimulated strongly the activity of the enzyme by 176.65% and 119.07% respectively, while inhibitory effects were found in the presence of Cu2+, Zn2+, Mg2+, and EDTA. The enzyme exhibited their stability toward surfactants (Triton X100, Tween 20, SDS), solvents (acetone,chloroform, hexane and toluene), oxidizing agent (H2O2) and Tesco Everyday Value®detergent with the residualactivity around 80%. It also demonstrated the removal activity of blood stain completely with supplementation of the 7 mg/ml detergent solution. The established characteristics of the enzyme indicated their potentiality for detergent application.